2021
DOI: 10.1177/0271678x211004307
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic analysis of extracellular matrix in mouse and human brain highlights relevance to cerebrovascular disease

Abstract: The extracellular matrix (ECM) is a key interface between the cerebrovasculature and adjacent brain tissues. Deregulation of the ECM contributes to a broad range of neurological disorders. However, despite this importance, our understanding of the ECM composition remains very limited mainly due to difficulties in its isolation. To address this, we developed an approach to extract the cerebrovascular ECM from mouse and human post-mortem normal brain tissues. We then used mass spectrometry with off-line high-pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…Mutations in the protein components of the brain ECM are associated with neurovascular dysfunction and the onset of sporadic cerebral small vessel disease [ 76 ]. Global proteomic analysis revealed that genes related to cerebrovascular diseases, such as COL4A1 , COL4A2 , VCAN and APOE , were significantly enriched in the cerebrovascular ECM network [ 77 ] and increased expression of fibronectin, perlecan and Col IV was observed in the early stages of AD [ 78 ]. The basement membrane degrades and thins after neurovascular dysfunction (e.g.…”
Section: Dysfunction Of the Nvumentioning
confidence: 99%
“…Mutations in the protein components of the brain ECM are associated with neurovascular dysfunction and the onset of sporadic cerebral small vessel disease [ 76 ]. Global proteomic analysis revealed that genes related to cerebrovascular diseases, such as COL4A1 , COL4A2 , VCAN and APOE , were significantly enriched in the cerebrovascular ECM network [ 77 ] and increased expression of fibronectin, perlecan and Col IV was observed in the early stages of AD [ 78 ]. The basement membrane degrades and thins after neurovascular dysfunction (e.g.…”
Section: Dysfunction Of the Nvumentioning
confidence: 99%
“…Genetic studies have revealed that most monogenic forms of SVD are caused by mutations in genes either encoding ECM proteins, or in proteins regulating ECM function (Joutel et al, 2016). In addition to extensive genetic support for a key role of the ECM in SVD, our recent work has found that genes related to SVD, including COL4A1 and COL4A2 , are significantly enriched in the cerebrovascular ECM network in both mouse and human brain (Pokhilko et al, 2021). To date, the mechanisms by which these ECM defects cause disease remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…ECM-focused proteomic methods have resulted in improved coverage of ECM proteins over traditional proteomic approaches that have been used for tissue atlas projects. To date, several M. musculus tissue types with accompanying disease states have been characterized, including lung, , heart, , mammary tissue, ,, lymph node, pancreatic islet, liver, kidney glomeruli, colon, cardiac tissue, skin, aorta, brain, pancreas, , myotendinous junction, and lung, to name a few. However, the reported studies do not cover the range of tissue types presented here.…”
Section: Introductionmentioning
confidence: 99%